حق الحصول على المعلومات في التشريعات الأردنية - المساعيد فرحان نزال (Journal of Legal Sciences, 2017)
The right to obtain information from the most sacred of rights and the most important and Olney represents spiritual humans importance, and building on it has the researcher spoke through Take the study for the content of this right and organization at the international and local level, as it meant the international conventions long ago this right and arranged for him sufficient guarantees rests countries in places much like Universal declaration of Human rights, but that this right has been many difficulties in the Jordanian legislation initially that the case came to what it is now, when the Jordanian legislator responded recently to popular demands and issued a guarantee the right of access to information law No. ( 47) for the year (2007), The researcher has reached a set of results, most notably the large number of restrictions on the use of this right in the Jordanian legislation, although privately Hashemite Kingdom of Jordan developed a special legislation for the right to access to information. The researcher presented several recommendations, among which was the need to reconsider the legislation regulating this right, and ease restrictions on the release of information.